Arrangierte Liebe - Leitfaden zur Sonderausstellung in der Ethnologischen Sammlung der Universität Göttingen - Racz, Julia (2013)
„Arranged Love“ deals with cross-cultural differences in understanding romantic love. All over the world we can find ideas of romantic love expressed by arts, poetry or material objects. The present publication attempts to show the varieties of romantic love exemplified by artifacts of Ethnographical collection of the Göttingen University’s Institute for Cultural and Social Anthropology.